2010
DOI: 10.7150/ijms.7.82
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan on expression of connexins at the early stage of atherosclerosis in rabbits

Abstract: Aim: to investigate effects of Losartan on expression of connexin 40 and 43 (Cx40 and Cx43), in arteries at the early stage of atherosclerosis in a rabbit model. Methods: A total of 28 male New Zealand white rabbits were divided into following groups: control group, high fat diet group, and Losartan group (10 mg/kg/day). Losartan was administrated in food for two weeks. Iliac arteries were obtained for immunohistochemistry, transmission electron microscopy, Western blot, and reverse transcriptase-polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Connexin-43 is a member of the connexin family, which forms intercellular gap junctions and is closely associated with inflammation. Connexin-43-knockdown alleviates the brain inflammation and glia activation induced by peripheral lipopolysaccharide injection ( 38 ). Connexin-43 is upregulated in the neointimal SMCs at an early stage of atherosclerosis in rabbits ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Connexin-43 is a member of the connexin family, which forms intercellular gap junctions and is closely associated with inflammation. Connexin-43-knockdown alleviates the brain inflammation and glia activation induced by peripheral lipopolysaccharide injection ( 38 ). Connexin-43 is upregulated in the neointimal SMCs at an early stage of atherosclerosis in rabbits ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the migration and proliferation of arterial SMCs, GJ transforms from the contractile phenotype to the synthetic phenotype. Recently, it has been shown that Cx43 expression is markedly enhanced in cultured SMCs at synthetic state when compared with that in those at the contractile state (Yeh et al, 1997;Song et al, 2009), and relatively high expression of Cx43 was observed in migrating and proliferating SMCs in the neointima following balloon injury (Ruan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Finally, Ang 1-7 and Ang II would exert opposite effects on the connexins of gap intercellular junctions, which may be altered by both AT-1 and Ang II and protected by Ang 1-7. [49]…”
Section: The Protective Action Of Ang 1-7 On Lung and Cardiovascular ...mentioning
confidence: 99%